Combining regenerative medicine strategies to provide durable reconstructive options: auricular cartilage tissue engineering. Issue 1 (December 2016) - Jessop, Zita; Javed, Muhammad; Otto, Iris; Combellack, Emman; Morgan, Siân; Breugem, Corstiaan; Archer, Charles; Khan, Ilyas; Lineaweaver, William; Kon, Moshe; Malda, Jos; Whitaker, Iain
Abstract Recent advances in regenerative medicine place us in a unique position to improve the quality of engineered tissue. We use auricular cartilage as an exemplar to illustrate how the use of tissue-specific adult stem cells, assembly through additive manufacturing and improved understanding of postnatal tissue maturation will allow us to more accurately replicate native tissue anisotropy. This review highlights the limitations of autologous auricular reconstruction, including donor site morbidity, technical considerations and long-term complications. Current tissue-engineered auricular constructs implanted into immune-competent animal models have been observed to undergo inflammation, fibrosis, foreign body reaction, calcification and degradation. Combining biomimetic regenerative medicine strategies will allow us to improve tissue-engineered auricular cartilage with respect to biochemical composition and functionality, as well as microstructural organization and overall shape. Creating functional and durable tissue has the potential to shift the paradigm in reconstructive surgery by obviating the need for donor sites.